Sports Participation and Quality of Life in Adolescents and Young Adults with Congenital Heart Disease. (8th September 2014) - Dean, Peter N.; Gillespie, Catherine W.; Greene, Elizabeth Anne; Pearson, Gail D.; Robb, Adelaide S.; Berul, Charles I.; Kaltman, Jonathan R.
Abstract Background Adolescents and young adults with congenital heart disease (CHD) are often restricted from physical activity and sports participation, which may have adverse effects. Objectives To determine the amount of physical activity, type of sports participation, and reasons for sports restrictions, and to evaluate the effect of sports participation on quality of life (QoL) in a cohort of patients with CHD. Methods Individuals with CHD aged 13–30 years were recruited at outpatient visits or via mailings. They completed a questionnaire addressing physical activity, sports participation, sports restrictions, and QoL (Pediatric Quality of Life Inventory). We also reviewed the patient's medical record. Results Of the 177 patients who responded (mean age 20 years), 31% have mild CHD, 40% have moderate CHD, and 29% have severe CHD. In the cohort, 52% participate in competitive sports, 25% recreational sports, and 23% no sports. Among patients with severe CHD, 29% participate in competitive sports that would be restricted by published guidelines (36th Bethesda Conference). After controlling for age, sex, CHD severity, residual hemodynamic disease, and comorbidities, participation in competitive sports and increased frequency of physical activity are independently associated with a higher QoL (P = .003 and P = .001, respectively). In an identical model, competitive sports participation and frequency of physical activity are associated with higher maximum predicted oxygen consumption (VO2) (n = 40; P = .002 and .02) and slightly lower body mass index (BMI) (P = .02 and .01). All findings were similar when analyses were stratified by recruitment method. Conclusions Patients with CHD commonly participate in competitive sports, and such participation is associated with higher QoL, improved exercise capacity, and lower BMI.